Blood CD3-(CD56 or 16)+ natural killer cell distributions are heterogeneous in healthy adults and suppressed by azathioprine in patients with ANCA-associated vasculitides - Merkt, Wolfgang; Salzer, Ulrich; Thiel, Jens; Jandova, Ilona; Bergner, Raoul; Venhoff, Ana C.; Venhoff, Nils (BMC immunology, 2021)
Cytotoxic Natural Killer (NK) cells are increasingly recognized as a powerful tool to induce targeted cell death in cancer and autoimmune diseases. Still, basic blood NK cell parameters are poorly defined. The aims of this study were 1) to establish reference values of NK cell counts and percentages in healthy adults; 2) to describe these parameters in the prototype autoimmune disease group ANCA-associated vasculitis (AAV); and 3) to investigate whether NK cell counts and percentages may be used as activity biomarkers in the care of AAV patients, as suggested by a preceding study.